Legal Remedies to End Exploitations against Vendees of Housing Units & Allowing Public Authorities to Intervene; a Case Study of the Residential Complexes in the Kurdistan Region of Iraq “An Analytical & Empirical Study” - Othman, Arez Mohammed Sediq (Sulaimani Journal for Humanities, 2021)
In the recent years and after the collapse of the previous Regime in 2003, there was a huge expansion in the scale of investment in real estate sector, in particular the residential complexes in many cities and towns in the Kurdistan Region of Iraq as the Kurdistan Investment law No.4 of 2006 has played a vital role in this regard by facilitating the procedures and decreasing routine in implementing such construction projects. However, the scale the scale of exploitation toward the vendees of housing unites is unbearable. Despite selling the unites in a very high price without any restriction whatsoever, by the relevant authorities, the content of the contracts were designed in such a way that there was no room for the vendees to recourse to the court when there is disobedience to the terms and conditions of the contract even if it is due to reasons out of vendee's control. The restricted powers of the public authorities in intervening and organizing the sector has also weakened the position of the vendees when the they are bound to the content of the contract despite having unfair terms and condition forced by the administration of the residential complex and public authorities does not have right to interfere. This study is an empirical study based on the content of ten typical contract signed between the vendees of the housing units and the residential complexes in three governorates of Kurdistan (Erbil, Sulaimani and Duhok) and conducting questionnaire with residences of such residential complexes. The terms and conditions of the signed contracts and responses of questionnaire have been analyzed under the light of the Iraqi legal system, particularly the Iraqi Civil Code No. 40 of 1951 and Law No. 61 of 2000 of the Ownership of Floors and Apartments. Methodology This research has undertaken analytical and field study; Individual interviews with relative stakeholders, field visit, questionnaires and literature reviews have been adopted as the main approach for conducting this research. The applicable legal provisions (such as Iraqi Civil Code, KRG's investment Law, Law No.61 of 2000 in Iraq) and various juristic opinions have been analyzed to reach out to research conclusion. Journal articles and books have been the m the main sources of literature review in this paper. Research importance In the recent years, due to the impetuses and enormous support by the government to the investors, investment in housing sector has been increased in Kurdistan Region of Iraq. The limited experience of investors in this field and the recentness of such investment caused many legal issues for the vendees of housing units. The loopholes in the related legislations and restricted restricted authorities from interference under the principle of freedom of contract have also worsened the issue. The vendees of housing units are facing many problems with the owners of the residential complexes when it comes to paying installments, the unfair terms and conditions of the contract and the services. This research will help public authorities to better organize this sector and work in favour of weak party. Research outline The paper has been divided into five main sections. The first section is dedicated to introduction followed by analyzing the questionnaire conducted by the researcher. In the third section, Examples of exploitative terms in the standard sale contracts in Kurdistan region of Iraq has been discussed. Fourth section has been devoted to the legal remedies by which public authority can intervene by vene by restricting the principle of freedom of contract. The paper ends up by a number of conclusions and recommendations which is explained in section five.